Analisis Sistem Antrean untuk Mengoptimalkan Pelayanan pada Coffeeshop Teman Sejalan .Co di Karanganyar - Christe Wiwin Wikaningrum; Sunarso Sunarso (Journal of Management and Social Sciences, 2024)
Teman Sejalan.co is a Coffeeshop located in Karanganyar and was established in December 2022. Operations in the Teman Sejalan.co Coffeeshop business certainly include from the initial order to pickup. This is related to the queuing system which must improve its service so that customers do not leave if there is a queue. This research uses the Single Channel Multiphase method which is in accordance with the current conditions of Teman Sejalan.co's servers and services. This data was obtained by going directly to the research object during the "Makgedebrews" event by calculating the customer queue time with the number of customers at that time being 103 customers. The results of the research regarding the server line service queue system with H1 and H2 were not proven to be true because the number of customers who were enthusiastic about the event held by Teman Sejalan.co. The use of 1 server lane is not optimal at events that are quite popular with customers which causes queues to pile up, so it is better to use 2 lanes at future events so that it is effective when it is busy.